A survey on the anxiety status of adolescents in minority concentration areas of Western Hunan—three years after the onset of the COVID-19 pandemic - Liu, Shengji; Zhang, Jiayi; Chen, Hongwei; Chen, Lijun (Frontiers in Public Health, 2025)
The COVID-19 pandemic has had a profound impact on adolescents of all ethnic groups in China, with most studies focusing on Han Chinese adolescents. This study assesses the anxiety status of 426 high school students aged 15–18 from the Tujia and Miao Autonomous Prefecture of Western Hunan, a minority concentration area, 3 years after the pandemic began, and explores its influencing factors. Using a cross-sectional survey design, data were collected via questionnaires covering anxiety, parental migration, parental education level, and individual general self-efficacy. Descriptive statistics, t-tests, correlation analysis, and linear regression were used for data analysis. The results revealed that: (1) the prevalence rate of anxiety symptoms among the surveyed subjects was 60.4%, with moderate anxiety accounting for 16.4% and severe anxiety for 5.3%; (2) female students scored significantly higher in anxiety than male students; (3) left-behind children exhibited significantly higher levels of anxiety symptoms compared to non-left-behind children; and (4) correlation and regression analyses indicated that gender, being a left-behind child, and general self-efficacy can effectively predict anxiety status. These findings demonstrate that 3 years after the outbreak of the pandemic, the anxiety status of high school students in the minority concentration areas of Western Hunan remains relatively severe, with females, left-behind children, and individuals with low self-efficacy being at higher risk. The study provides a deeper understanding of the psychological conditions of minority adolescents in Western Hunan and offers scientific evidence for the development of targeted mental health intervention measures.